Business and economics of port management : an insider's perspective - Yap, Wei Yim (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Business and Economics of Port Management is a comprehensive but concise textbook for insights into the workings of port industry from the business and economics perspectives. The book examines port management from various entities which includes the government, port operator, shipping line, logistics companies and other port service providers. It provides in-depth discussions on strategic issues, challenges and disruptions that are faced by this industry. Given the uniqueness of each port and international nature of the port business, the book comes with useful case studies and lessons from different port regions around the world to enlighten key lessons on challenges and issues faced by port managers, developers and regulators. It also touches upon publicly available information sources to facilitate the decision making process and contribute to better outcomes for the industry, government and the public at large. Anyone who is approaching the subject matter for the first time will gain utmost understanding of how ports are critical in the global economy and societal well-being"--
OCLC-licensed vendor bibliographic record.
Keywords: Harbors -- Management; BUSINESS & ECONOMICS / Economics / General